Serum and Cerebrospinal Fluid Levels of Colistin in Pediatric Patients - Antachopoulos, Charalampos (American Society for Microbiology (ASM), 2010)
Using a liquid chromatography-tandem mass spectrometry method, the serum and cerebrospinal fluid (CSF) concentrations of colistin were determined in patients aged 1 months to 14 years receiving intravenous colistimethate sodium (60,000 to 225,000 IU/kg of body weight/day). Only in one of five courses studied (a 14-year-old receiving 225,000 IU/kg/day) did serum concentrations exceed the 2 μg/ml CLSI/EUCAST breakpoint defining susceptibility to colistin for Pseudomonas and Acinetobacter. CSF colistin concentrations were <0.2 μg/ml but increased in the presence of meningitis (∼0.5 μg/ml or 34 to 67% of serum levels).